A Research Proposal of Point of Sale For Kuya Romeo’s Kitchenette: Sales Analysis: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Almost all of their operations in the business industry rely on technology or a system that can assist them in simplifying transactions. Kuya Romeo's Kitchenette uses a manual system that involves a lot of paperwork and cannot immediately produce a sales report. To address the issue, a Point of Sale System, Sales Analysis, was created to generate accurate sales reports and assist business owners in managing their business transactions efficiently. The system was developed using the Software Development Life Cycle (SDLC), where each phase is processed and completed one at a time. The researchers interviewed the client to be able to provide a solution to their problems based on a conceptual and regulatory framework as well as the literature that is associated with sales analysis using a point-of-sale system. The study outcomes revealed that the Point of Sale System: Sales Analysis solved all of the client's difficulties, and the system features' results are functional. It means that the business owner can now track their sales report while staff save time, which will streamline and improve the business process. The researcher aims to provide Kuya Romeo's Kitchenette with a more accessible and modern alternative for making their sales. The proposed system, "Point of Sale System: Sales Analysis," was found to be fully functional based on the results of the case assessments. It shows that the system operates per its project objectives and can provide an accurate report that analyses the sales.
Keywords: Point of Sale; Sales Analysis; System Development Life Cycle